Evaluation of Kenyan Bentonite Clay as Geothermal Well Drilling Mud - Weramwanja, Peter M.; Musuva, Jeremiah M.; Kihiu, John M.; Borode, Joseph O.; Olubambi, Peter A.; Mibei, Geoffrey K. (My University, 2015)
The quest for the development of geothermal plants with capacities up to 10,000 MWe in Kenya has recently placed greater demand on bentonite clay. Bentonite clay is at present largely imported into the country at the great expense of foreign exchange. There is thus, need to source for bentonite clay locally. In this study, the suitability of Kenyan bentonite, in its raw form for possible use in well drilling was evaluated. Selected samples from Isinya, Amboseli and Lewa were characterized by scanning electron microscopy, energydispersive x-ray, x-ray diffraction and x-ray fluorescent to determine the microstructural, elemental, mineralogical and chemical composition respectively. Moreover, rheological analyses were performed on raw samples to evaluate the bentonite clay's suitability in geothermal well drilling applications. Results revealed that chemical, mineralogical and rheological properties of unmodified clays are not adequate for use in drilling application. However, by modification of Isinya and Amboseli clays, the composition of calcium may be reduced significantly leading to improved flow properties required in drilling mud.
Keywords: Montmorillonite; Bentonite; Rheological; Drilling mud